Circulating semicarbazide-sensitive amine oxidase is raised both in Type I (insulin-dependent), in Type II (non-insulin-dependent) diabetes mellitus and even in childhood Type I diabetes at first clinical diagnosis - Boomsma, F.; van den Meiracker, A. H.; Winkel, S.; Aanstoot, H. J.; Batstra, M. R.; Man in ’t Veld, A. J.; Bruining, G. J. (Diabetologia, 1999)
Plasma semicarbazide-sensitive amine oxidase is raised in patients with Type I (insulin-dependent) diabetes mellitus. It has been suggested that this enzyme is involved in the development of microvascular damage through its ability to convert amines (e.g. methylamine and aminoacetone) into aldehydes, hydrogen peroxide and ammonia. Plasma semicarbazide-sensitive amine oxidase was found to be equally raised both in patients with Type I diabetes (n = 73) and Type II (non-insulin-dependent) diabetes mellitus (n = 88) compared with control subjects (621 +/- 209 and 619 +/- 202 vs 352 +/- 102 mU/l, p < 0.0001) and to correlate in multiple regression analysis with HbA1c. Since the enzyme could protect the islets from the inhibitory effects of methylamine on insulin secretion, we also tested sera of 100 children, collected consecutively at first diagnosis of Type I diabetes, for semicarbazide-sensitive amine oxidase. The activity was greatly increased compared with serum values of 76 control (siblings) children (757 +/- 300 vs 455 +/- 138 mU/l, p < 0.0001), but not associated with HbA1c. Our study confirms the increase of plasma semicarbazide-sensitive amine oxidase in Type I diabetes and extends this finding to Type II diabetes as well as to childhood Type I at first clinical diagnosis. In the last case increased enzyme activities could serve to protect the islets from inhibitory effects of methylamine but cause damage by generation of hydrogen peroxide, aldehydes and ammonia. In the long run the increased enzyme activities could also contribute to vascular damage by direct cytotoxic action on endothelial cells, including increased oxidative stress and glycosylation of proteins.